Pengaplikasian Program Vitamin Ternak TeBing (Temulawak Kambing) di Desa Kalisat Kecamatan Ijen Kabupaten Bondowoso - Akhmad Munif Mubarok; Liza Ayu Dwi Kharisma; Mahega Cindya Firliyanti; Achmad Ismail; Yusnan Hadi Mochtar; Kurniawati Sa’adah (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Goat farming in Kalisat Village continues to face issues regarding low productivity due to traditional husbandry practices and a lack of nutritional supplementation. This community service program in Kalisat Village, Ijen District, Bondowoso Regency, aimed to improve goat health and productivity through the implementation of "TeBing" (Temulawak-based goat vitamin), a supplement utilizing local resources. The methods employed included observation, interviews, Focus Group Discussions (FGD), outreach activities, training on vitamin production, and monitoring and evaluation. The results demonstrated an improvement in the farmers' understanding and skills regarding the independent production and application of TeBing vitamins. The distribution and monitoring of Temulawak (Java ginger) planting stock supported the sustainable supply of local raw materials. This program contributes to strengthening farmer self-reliance and fostering a goat farming system that is healthier, more productive, and sustainable.